111 Kikuchi-Fujimoto disease in childhood onset lupus: a case series from a tertiary care center in north india. (April 2019) - Chaudhary, Himanshi; Suri, Deepti; Rawat, Amit; Gupta, Anju; Jindal, Ankur; Guleria, Sandesh; Radotra, Bishan; Singh, Surjit
Abstract : Background: Kikuchi-Fujimoto disease (KFD) is a rare disorder described mostly in adolescents and young adults. It is a great mimicker, has a diverse clinic-laboratory profile and appears to be an under-recognized disease entity, especially in children. Methods: We report 6 children who presented with fever and lymphadenopathy and had findings on fine needle aspiration cytology (FNAC) and/or histopathology that were compatible with a diagnosis of KFD. Two amongst these 6 patients developed lupus. Results: Case 1: A 7 year old boy was admitted with complaints of high-grade fever and left submandibular lymph node swelling for 2 weeks. A possibility of suppurative lymphadenitis was kept and he was treated with antimicrobials. He was the youngest born to a consanguineously married couple who had lost two children previously to a lupus-like illness. The striking family history suggested the possibility of a monogenic form of lupus (early complement deficiency). C1q levels were found to be significantly low (C1q level: 0.27 mg/L; normal (102–170 mg/L)) Genetic analysis revealed a nonsense mutation in the C1QA gene (c.622C>T Q208X). Investigations revealed mild anemia (hemoglobin:107 gm/L) and elevated erythrocyte sedimentation rate (ESR:68 mm) in 1 st hour and C-reactive protein (CRP:8 mg/dl). An excision biopsy of the lymph node showed necrotizing histiocytic lymphadenitis consistent with KFD. Immunological work-up revealed Antinuclear antibodies (ANA) 2+speckled pattern on immunofluorescence; no anti ds-DNA antibodies; no antiphospholipid antibodies. He was treated with immunosuppressants and twice-daily fresh frozen plasma. Fever subsided in 5 days and lymph nodes regressed in 2 weeks. Case 2: A 12-year-old boy presented with fever of 7 months duration and generalized seizures followed by altered sensorium. He was treated in lines of subacute meningo-encephalitis. As there was no response to treatment he was referred to our institute. On examination, he had malar rash, frontal alopecia and bilateral, multiple enlarged cervical lymph nodes. Laboratory investigations revealed anemia, elevated ESR, high CRP and low levels of C3 and C4. ANA was positive (3+speckled); anti-dsDNA titers were 130 IU/ml (normal-<60 IU/ml); FNAC from lymph node revealed features consistent with KFD. A diagnosis of lupus and KFD was made andhe was started on oral prednisolone along with hydroxychloroquine. Fever subsided in 3 days and lymph nodes regressed in 2 weeks. There has been no recurrence of KFD on follow-up over the next 6 years. Conclusions: The association of KFD with childhood onset lupus is unusual. Early recognition of this entity can prevent diagnostic and therapeutic errors Funding Source(s): nil. Kikuchi-Fujimoto disease in childhood onset lupus: a case series from a tertiary care center in North India